Hydrogen storage properties of the CeH_2 doped Li-Mg-N-H/NaAlH_4 system - 张旭刚 李志念 王树茂 米菁 蒋利军 吕芳 刘晓鹏 (Journal of rare earths, 2011)
The mutual destabilization between complex hydrides and lithium amide has been comprehensively reported. In this paper, CeH2 doped Li-Mg-N-H/NaAlH4 composite was successfully synthesized by ball milling Li-Mg-N-H mixture and NaAlH4 in a molar ratio of 1：2. It was found that a total of 5 wt.% of hydrogen could be desorbed from the newly synthesized composite with a three-step reaction. Temperature-programmed-desorption （TPD） measurements showed that the composite ball milled for 10 min began to desorb hydrogen below 100 °C, which was about 75 °C lower than the pristine materials. XRD analysis revealed that NaAlH4 firstly reacted with LiH to yield Na2LiAlH6 and Al below 150 °C, then the newly developed Na2LiAlH6 reacted with Mg（NH2）2 to form NaH, Al, and Li2MgN2H2 in the temperature range of 180–250 °C. From 200 to 300 °C, the newly formed Al and Li2MgN2H2 reacted further to form Li2NH and some stable phase （AlN and Mg3N2）. The H-cycling properties of the composite were further investigated by a standard Sievert’s type apparatus at 150, 200 and 250 °C, respectively. Finally, the reversibility of the newly synthesized composite was discussed.